Self-Management of Multiple Chronic Conditions by Community-Dwelling Older Adults: A Concept Analysis - Anna Garnett MSc, RN; Jenny Ploeg PhD, RN; Maureen Markle-Reid PhD, RN; Patricia H. Strachan PhD, RN (SAGE Publishing, 2018)
The proportion of the aging population living with multiple chronic conditions (MCC) is increasing. Self-management is valuable in helping individuals manage MCC. The purpose of this study was to conduct a concept analysis of self-management in community-dwelling older adults with MCC using Walker and Avant's method. The review included 30 articles published between 2000 and 2017. The following attributes were identified: (a) using financial resources for chronic disease management, (b) acquiring health- and disease-related education, (c) making use of ongoing social supports, (d) responding positively to health changes, (e) ongoing engagement with the health system, and (f) actively participating in sustained disease management. Self-management is a complex process; the presence of these attributes increases the likelihood that an older adult will be successful in managing the symptoms of MCC.